Membangun Karakter Bangsa Melalui Pendidikan Nilai Sejak Dini - Nada Nabila; Rani Warni; Deni Marlina (Lembaga Pengembangan Kinerja Dosen, 2025)
A moral and cultured society is largely built on national character, and as childhood is the prime time for personality formation that will influence the caliber of subsequent generations, it is imperative that character integrity be instilled early. This study analyzes pertinent references using aliterature study method and a qualitative methodology. Instilling national ideals and producing a generation equipped to face today's issues with resilience The main way to develop character is through contextual, cooperative, and consistent .